Effect of Psoriasis on Quality of life - Basnet, Binamra; Ranjit, Annu; Subedi, Anil; Shrestha, Shristi; Neupane, Saraswoti (Nepal Journal of Dermatology, Venereology & Leprology, 2018)
Introduction: Psoriasis is one of the common skin disorders which has a significant distressing effects on patients due to its chronicity, joint involvement, therapy related side effects and its impact on physical appearance. Objective: To find out impairment in quality of life among patients with psoriasis. Materials and Methods: Patients attending the Dermatology outpatient department of Gandaki Medical College were recruited for the study from December 2016 to July 2017. Dermatology Life Quality Index (DLQI) was used to assess the psychosocial involvement. Results: Significant increase in DLQI scores depicting graver psychosocial involvement in females compared to males was observed (p=0.038). Comparison between severity of disease and DLQI scores showed a positive correlation but was not statistically significant (r=0.22 & p=0.187). When we compared the type of psoriasis with severity of disease, chronic plaque psoriasis showed significant statistical correlation (p=0.003). Conclusion: Females tend to experience significant impairment in quality of life compared to males. Further studies with more sample size are needed to consolidate or rectify our findings.